Understanding the Role and Impact of Poly (Ethylene Glycol) (PEG) on Nanoparticle Formulation: Implications for COVID-19 Vaccines - Padín-González, Esperanza; Lancaster, Pearl; Bottini, Massimo; Gasco, Paolo; Tran, Lang; Fadeel, Bengt; Wilkins, Terence; Monopoli, Marco P. (Frontiers in Bioengineering and Biotechnology, 2022)
Poly(ethylene glycol) (PEG) is a widely used polymer in a variety of consumer products and in medicine. PEGylation refers to the conjugation of PEG to drugs or nanoparticles to increase circulation time and reduce unwanted host responses. PEG is viewed as being well-tolerated, but previous studies have identified anti-PEG antibodies and so-called pseudoallergic reactions in certain individuals. The increased use of nanoparticles as contrast agents or in drug delivery, along with the introduction of mRNA vaccines encapsulated in PEGylated lipid nanoparticles has brought this issue to the fore. Thus, while these vaccines have proven to be remarkably effective, rare cases of anaphylaxis have been reported, and this has been tentatively ascribed to the PEGylated carriers, which may trigger complement activation in susceptible individuals. Here, we provide a general overview of the use of PEGylated nanoparticles for pharmaceutical applications, and we discuss the activation of the complement cascade that might be caused by PEGylated nanomedicines for a better understanding of these immunological adverse reactions.